PEMBUATAN PLANG JALAN DAN PENAMBAHAN PAPAN NAMA GAPURA SEBAGAI UPAYA PENINGKATAN IDENTITAS DAN AKSEBILITAS DI KAMPUNG MANDIRI JAYA - ABU BAKAR; Zainal Arifin; Rochmatullah; Aris Siletty (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
Village Mandiri Jaya is located in Wania District in Mimika regency which faces limited means of identity and information from the public in the form of road signs and gate signboards. This condition causes low accessibility of the community and navigation difficulties for newcomers as well as the weak image of the village as a regional identity. Through the kuliah Kerja Nyata (KKN) program which focuses on community service, STIE Jambatan Bulan Timika students together with the village and local residents carry out activities to make road signs at strategic points and add signage to the Village Gate. The method of activity used is field observation to identify problems, discussion and coordination with the village and the community, training and technical briefing, implementation of mutual cooperation with the village and the community, up to the evaluation and reporting stage. The results of the activity showed an increase in village identity, ease of access, and regularity of space. In addition to producing physical outputs in the form of road signs and gate signage, this program also provides a social impact in the form of increased participation and a sense of community ownership of the environment. This activity proves that collaboration between universities, village parties, and community members can strengthen the identity of the region and become a model for sustainable service.